The Impact of Emotional Intelligence, Depression, Anxiety and Stress on Work-Life Balance - Baker, Rogis; Jaaffar, Amar Hisham; Sallehuddin, Hasimi; Saudi, Nur Surayya Mohd; Mohamad, Mohd Hamran; Ghani, Sayuti Ab (International Journal of Psychosocial Rehabilitation, 2020)
The increasing issues relating to emotional intelligence, depression, anxiety and stress have made work-life balance a problem in society. This article focuses on understanding the impact of emotional intelligence, depression, anxiety and stress on the work-life balance. This article also presents empirical evidence based on previous studies which investigated the relationship between emotional intelligence, depression, anxiety and stress and work-life balance. The results of previous studies found that there is a significant relationship between these elements. As such, an organization's desire to address issues related to emotional intelligence, depression, anxiety and stress could help improve the balance between work and family life resulting in the enhanced well-being of workers.